A novel cobalt(II) metal–organic framework based on an unprecedented ribbon-shaped secondary building unit - Meng, Wei; Xu, Shuang; Zhang, Zhengrui; Yu, Shuqi; Yu, Jikang; Dai, Lei; Wang, Ling; Hou, Hongwei (Inorganic chemistry communications, 2016)
A novel 3D metal–organic framework (MOF) {[Co2.5(dcpp) (μ3-OH) (μ-H2O)]·H2O}n (H4dcpp=4,5-bis(4′-carboxylphenyl)-phthalic acid) with unprecedented ribbon-shaped secondary building units (SBUs), has been synthesized and characterized by single-crystal X-ray diffraction, elemental analysis, and IR. In addition, the thermal stability and magnetic behavior of the complex were also investigated. This work reports a novel cobalt(II) metal–organic framework based on an unprecedented ribbon-shaped secondary building unit. The complex represents the first example of MOF built from high nuclear ribbon-shaped SBU. Furthermore, the study of magnetic property indicated that dominant antiferromagnetic coupling interactions existed between the adjacent Co(II) centers. [Display omitted] •Multidentated carboxylic 4,5-bis(4′-carboxylphenyl)-phthalic acid as the linker•A novel cobalt(II) MOF with an unprecedented ribbon-shaped SBU•Antiferromagnetic interactions between the Co(II) centers